INVESTIGATION OF RISK FACTORS, TOPOGRAPHIC LOCATION AND STROKE MECHANISMS OF UNILATERAL ISOLATED AND POSTERIOR CEREBRAL ARTERY THALAMIC INFARCTS - Uslu, Ferda; Gokcal, Elif; Sengul, Yildizhan; USLU, FERDA (My University, 2019)
Aim - In this study, we aimed to examine the risk factors, topographic features and stroke mechanisms of acute ischemic unilateral infarcts of thalamus.